Implicit practice for technique adaptation in expert performers - Rendell, M. A.; Farrow, R.; Masters, R.; Plummer, N. (International Journal of Sports Science and Coaching, 2011)
Coaches traditionally rely on explicit approaches (e.g., instruction, video feedback) to adapt technique in skilled athletes. While such methods can generate relatively rapid learning outcomes, the resultant technical execution is susceptible to breakdown under competition pressure. An alternative approach is to use `implicit motor learning` in which adaptations occur without conscious knowledge of the underlying rules and the newly learned skill is less likely to breakdown under pressure. However, research has not demonstrated whether implicit motor learning can be used to adapt technique in athletes whose skills are already expert. Two expert netball players undertook a 6-week training intervention in which they practiced shooting to an adapted ring (hypothesised to cause an advantageous increase in the trajectory of shots) while responding to a concurrent secondary task (high and low pitched tones). Pre- and post-testing of shooting performance revealed a change in the maximum ball height following the intervention. The players showed no increase in generic or episodic knowledge, remained robust under secondary task load, and were unable to differentiate between pre- and post-test video footage of their shots. These measures indicate that players were unaware of the knowledge underlying adaptations of their technique, but equally highlight the need for further empirical investigation of implicit practice in expert performers.